Tradisi Keilmuan Ramadhan di Pondok Pesantren Madinatul Ulum Al-Irsyadiyah Bogor - Umam, Fuadul Fuad; Muhammad Syahrul Hasan, Hasan; Ratna , Sari; Fida, Syahriyah (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2025)
This study examines the Ramadhan scholarly tradition at Pondok Pesantren Madinatul Ulum Al-Irsyadiyah in Cibeuteung Udik, Ciseeng, Bogor Regency. Employing a historical anthropological and descriptive-analytical approach, it aims to uncover and document the evolution and practices of Islamic scholarship during the holy month of Ramadhan in this pesantren. The research focuses on the crucial role of Kyai Abdul Hadi in establishing and developing the pesantren, and the leadership transition to Gus Farid following Kyai Abdul Hadi's passing in 2020. Findings reveal that the Ramadhan scholarly tradition includes kitab study, Qur'anic recitation, and Arabic grammar instruction, with distinct curricula for male and female students. A unique aspect is the involvement of three main teachers—Gus Farid, Ustadz Hayat, and Ustadz Syahidin—each bringing diverse educational backgrounds, enriching the students' learning experience. This study provides a detailed picture of the scholarly dynamics in the pesantren during Ramadhan, including teaching methods, studied materials, and students' responses to this tradition. It contributes significantly to our understanding of the role of pesantren in preserving and developing Islamic scholarly traditions in Indonesia, particularly during Ramadhan.